Search for a low-mass scalar Higgs boson decaying to a tau pair in single-photon decays of Υ(1S) - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
We search for a low-mass scalar CP-odd Higgs boson, A0, produced in the radiative decay of the upsilon resonance and decaying into a τ+τ− pair: Υ(1S)→γA0. The production of Υ(1S) mesons is tagged by Υ(2S)→π+π−Υ(1S) transitions, using a sample of (98.3±0.9)×106 Υ(2S) mesons collected by the BABAR detector. We find no evidence for a Higgs boson in the mass range 3.5≤mA0≤9.2 GeV, and combine these results with our previous search for the tau decays of the light Higgs in radiative Υ(3S) decays, setting limits on the coupling of A0 to the b¯b quarks in the range 0.09-1.9. Our measurements improve the constraints on the parameters of the next-to-minimal-supersymmetric Standard Model and similar theories with low-mass scalar degrees of freedom.